2014
DOI: 10.1097/qad.0000000000000421
|View full text |Cite|
|
Sign up to set email alerts
|

Long-acting three-drug combination anti-HIV nanoparticles enhance drug exposure in primate plasma and cells within lymph nodes and blood

Abstract: Insufficient HIV drug levels in lymph nodes have been linked to viral persistence. To overcome lymphatic drug insufficiency, we developed and evaluated in primates a lipid-drug nanoparticle containing lopinavir, ritonavir, and tenofovir. These nanoparticles produced over 50-fold higher intracellular lopinavir, ritonavir and tenofovir concentrations in lymph nodes compared to free drug. Plasma and intracellular drug levels in blood were enhanced and sustained for 7 days after a single subcutaneous dose, exceedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 18 publications
0
54
0
Order By: Relevance
“…Freeling et al produced solid lipid nanoparticles containing boosted lopinavir (L/r) and TFV. Using macaque model, the investigators demonstrated enhanced penetration of the ARV drugs into lymph nodes compared to that of free drugs (10,27). Other investigators have used wet-milled technique to develop FTC crystals that boosted protease inhibitor efficacy in humanized mice when linked with folic acid (28,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Freeling et al produced solid lipid nanoparticles containing boosted lopinavir (L/r) and TFV. Using macaque model, the investigators demonstrated enhanced penetration of the ARV drugs into lymph nodes compared to that of free drugs (10,27). Other investigators have used wet-milled technique to develop FTC crystals that boosted protease inhibitor efficacy in humanized mice when linked with folic acid (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…In ARV encapsulations into a nanoparticle formulation, drugs are released from the nanoparticles over an extended period, allowing for once-monthly or longer treatment modalities (7)(8)(9). However, the encapsulation of water-soluble ARV drugs, namely, NRTIs such as FTC, has been difficult, and the encapsulation efficiency has been quite low (10). Our laboratory has been working on solving this problem.…”
mentioning
confidence: 99%
“…The results of this study suggested that Tef disoproxil fumarate-NF acted as an LA drug via sustained release of Tef to show coitus-independent HIV-1 vaginal protection modality. 24 Freeling et al 25 developed an NF containing three LA anti-HIV drugs (lopinavir, ritonavir, and Tef) loaded in a lipid nanoparticle for longer exposure in primate plasma cells within lymph nodes (persistent HIV reservoirs) and blood to cure HIV infection. This developed NF showed 50-fold higher intracellular drug concentration in lymph in comparison to free drug administration.…”
Section: Kaushik Et Almentioning
confidence: 99%
“…Thus, the presented NF can be used as oral therapy for HIV at the periphery level. 25 Roy et al 26 developed an NF (140 nm) to eradicate HIV infection in the gut-associated lymphoid tissue (GALT), a reservoir of early HIV infection and host-pathogen interaction. The complex physiology of GALT resisted delivery of conventional anti-HIV drugs.…”
Section: Kaushik Et Almentioning
confidence: 99%
“…The availability of a simple, sensitive, selective, efficient, and validated assay has enabled reliable quality control in the production of longacting anti-HIV combination drug nanoparticles containing LPV, RTV, and TFV and the in vivo pharmacokinetic analysis of the nanoparticles and their distribution to the lymphoid tissue and blood mononuclear cells (16).…”
mentioning
confidence: 99%